1981
DOI: 10.1002/bjs.1800680812
|View full text |Cite
|
Sign up to set email alerts
|

Cimetidine and the potential risk of postoperative sepsis

Abstract: The gastric microflora of patients receiving cimetidine for duodenal ulceration has been investigated and the results compared with those from a group of untreated patients. Cimetidine-induced hypochlorhydria allows bacterial proliferation in the stomach; 75 per cent of aspirates from 44 fasting patients taking cimetidine 1 g daily were found to contain bacteria 2--4 h after the last dose. Of 41 patients taking cimetidine 400 mg at night, 34 per cent still had bacteria in their aspirates 12--13 h later. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

1982
1982
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 8 publications
0
12
1
Order By: Relevance
“…cimetidine) or proton pump inhibitors, the bacteria may also multiply excessively in the gastric juice. When this is the case, the risk of agents invading the gastric wall is significantly higher [8,9]. In some patients the gastric mucosa is damaged due to the effect of alcohol, chemicals, drugs, bacterial toxins from inflammations at different sites, mycotic infection, chronic gastritis, lowered pH of gastric acid and disseminated strongyloidosis [2,[10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…cimetidine) or proton pump inhibitors, the bacteria may also multiply excessively in the gastric juice. When this is the case, the risk of agents invading the gastric wall is significantly higher [8,9]. In some patients the gastric mucosa is damaged due to the effect of alcohol, chemicals, drugs, bacterial toxins from inflammations at different sites, mycotic infection, chronic gastritis, lowered pH of gastric acid and disseminated strongyloidosis [2,[10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…(Deane et al, 1980;Ruddell et aL, 1980;Muscroft et al, 1981a;Stockbrugger et al, 1981). Important to any potential role in carcinogenesis is the metabolic activity of such bacteria and the length of time for which they maintain that activity in the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were studied 10-5 hr after their last (evening) cimetidine dose in preference to immediately after their morning dose. Muscroft et al (1981a) showed that of 41 patients taking cimetidine, 400 mg at night, 34% had significant bacteria in their aspirates 12-13 hr later, whilst Longstreth, Go and Malagelada (1976) found three out of six patients to be anacid 8 hr after a single 400 mg cimetidine dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bacterial overgrowth of the stomach might increase the formation of potentially carci nogenic nitrosamines. However, this has also been observed during cimetidine treatment [20][21][22][23][24][25]. Long-term and widespread use of the Hi-receptor blockers has not been shown to cause an increased incidence of gastric carcinoma.…”
Section: Duodenal Ulcermentioning
confidence: 95%